In vivo determination of sex and reproductive status of Octopus tehuelchus (Cephalopoda: Octopodidae) by ultrasound techniques - Mercedes Berrueta; Andrea V. López; Mariela Radonic; Barbara Gorriti Goroso; Eddie Aristizabal (Marine and Fishery Sciences)
In recent years, studies on the cultivation of various species of cephalopods have grown with the aim of diversifying the supply of aquaculture products in the world market. Ultrasound images constitute a non-invasive method that has been utilized to determine sex and maturity stages in fish, being a useful tool for the management of captive broodstocks. The objective of this work was to evaluate the effectiveness of ultrasound techniques for the identification of sex and reproductive status of the small Patagonian octopus Octopus tehuelchus. Observations were carried out with a portable ultrasound machine (Sono Site Ultrasound System) and a transducer (10-5 Mhz) in eight anesthetized individuals. In ventral view, the testis had a spherical, homogeneous and compact appearance, while the spermatophore complex appeared as a hyperechoic structure with respect to the testis, highlighting the presence of spermatophores in mature individuals. In females, the dorsal view allowed to identify a granular-appearance ovary with anechogenic areas, indicating a maturing ovary. Ultrasounds allowed unequivocal sexing. In this way, the ultrasound technique was a practical and non-invasive method for determining sexes and gonadal maturation in live specimens of O. tehuelchus.